The Causal Impact of Education on Mental Health and Explanatory Mechanisms - Aysun Hiziroglu Aygun; Abdullah Tirgil (ZBW – Leibniz Information Centre for Economics, 2024)
This paper investigates the causal relationship between education and mental health in Turkey. We rely on the quasi-experimental setting created by the 1997 compulsory education reform that raised the compulsory years of schooling from five to eight years. Using regression discontinuity design, we use the birth year to indicate reform exposure and identify the causal effects of longer years of schooling on mental health. Our results demonstrate a sizable negative impact of education on the mental health scale. We present evidence that the reform had a more adverse effect on men's mental health. There is also heterogeneity by the place of residence, as the longer school years led people who live in urban areas to experience worse mental health outcomes. By investigating possible mechanisms, we show that those with at least a middle school education did not invest more in their health than those without a middle school diploma. We explain the evidence for the adverse effects of education on mental health, especially experienced by those who face higher competition in the labor market, by the lack of an increase in household income despite the longer years in school.
Keywords: I12; I26; I28; 330; mental health; MHI-5; regression discontinuity design; compulsory schooling law; education policy; Turkey